Compartmental modeling and analysis of the effect of β-amyloid on acetylcholine neurocycle via choline leakage hypothesis. (February 2021) - Mustafa, Ibrahim; Awad, Asmaa; Fgaier, Hedia; Mansur, Abdalla; Elkamel, Ali
Abstract: In this paper, the effect of β-amyloid (Aβ) oligomer aggregates on Acetylcholine (ACh) neurocycle of human brain and its relation to Alzheimer's disease (AD) are investigated through a two-enzyme/two-compartment (2E2C) diffusion mathematical model whereby compartment 1 represents the presynaptic neuron while compartment 2 represents the postsynaptic neuron and postsynaptic cleft. It is found that Aβ aggregates induce choline leakage from the presynaptic neurons (compartment 1) leading to a reduction in choline content in both compartments. The lowering in choline levels in each compartment is promoted with the increase in the inlet Aβ oligomers which create more channels and pores in the presynaptic membrane. In addition, it is found that both the rates of ACh synthesis and hydrolysis were affected negatively by the increase in the levels of Aβ oligomers. Furthermore, the levels of ACh in both compartments decreased while the level of Aβ oligomers increased. However, the acetate concentration in compartment 1 increased but the acetate level in compartment 2 decreased. These results are compatible with the low levels of both ACh and choline in the neuron tissues of Alzheimer's disease (AD) brains through choline leakage hypothesis. Also, the model shows the significant effect of inhibiting Aβ aggregation as a promising therapeutic mechanism to mitigate cholinergic diseases. The model suggests that Aβ oligomers exert neuroinflammatory and toxic effect against the ACh neurocycle. The paper suggests that development of therapeutic agents capable of inhibiting toxic Aβ aggregations and maintaining choline substrates in neurons is necessary to provide a neuroprotective effect, cholinergic transmission, and maintain reasonable levels of ACh.